Strip Cultures Finding America in Las Vegas (Book collections on Project MUSE., 2015)
The Project on Vegas shows how the Las Vegas Strip concentrates and magnifies American culture's core truths. Among others, the Strip's buffets, surveillance, large scale branding and consumption, and transformation of nature reflects larger trends and practices throughout America. Includes over 100 photographs by Karen Klugman.